(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
Aim: To determine the Socio-Economic Determinants of Latrine Use in Imenti North Sub County, Meru County, Kenya. Objective: To examine the social economic factors influencing latrine use among the residents of Imenti North Sub-County, Meru County, Kenya. Introduction: Sanitary Latrine access is crucial for public health and sustainable development, for significant reduction of morbidity and mortality from diseases like diarrhea. Despite global efforts, 3.6 billion people lacked access to safely managed sanitation services in 2020, with sub-Saharan Africa and rural areas disproportionately affected. In Kenya, only 33% of the population has improved sanitation, with significant disparities across regions. Study Area and Population: The study was conducted in Imenti North Sub County, Meru County, Kenya, with a population of 548,161 and 57,668 households. The target sample was 396 households, calculated using the Yamane formula, and data was collected through questionnaires, observation checklists, and interviews. Methodology: Cross-sectional descriptive study design incorporating both quantitative and qualitative methods was employed. Purposive and cluster sampling techniques were used to obtain appropriate sample size. From each cluster, simple random sampling technique was utilized to select respondents. Data analysis was conducted using SPSS Version 26 to generate descriptive and inferential statistics. Ethical approvals were obtained and permits sought to ensure participant confidentiality. Results: The response rate was 97%, with 387 fully completed questionnaires. Key findings included: Household Characteristics, 72% of household heads were males. Most respondents had primary education (41%), and over half were not formally employed, indicating economic instability. Sanitation Practices: 68% of households had 4 - 8 occupants, affecting latrine hygiene and use. 77.8% financed latrine construction from personal resources, and health education was a significant motivator (42.9%).Challenges: Major barriers to latrine use included unhygienic conditions (51.7%) and distance (29.2%). The main obstacles to latrine ownership were lack of land (29.5%) and financial constraints (22.2%). Inferential Statistics: Significant factors influencing latrine use included household density, cleanliness, hand wash station availability, and privacy, all showing p-values = 0.000< 0.05. Conclusion: Socio-economic factors, including education, income, and household size, significantly impact latrine use in Imenti North. The study concludes that addressing these issues through targeted health education, affordable sanitation solutions, and community engagement is crucial for improving sustainable sanitation practices. Keywords: Sanitation, Latrine Use, Socio-Economic Factors, Public Health, Rural Sanitation